To solving the problem of the “last mile” of the cable TV distribution network - MAMMADOV, Isa; AFANDIYEV, Ilham; MURADSADEH, Elvin (International Journal of Innovative Research and Scientific Studies, 2025)
Isa Mammadov1 The article studied the problem of using broadband radio access technology to solve the "last mile" problem in the cable television distribution network in Baku and the Absheron Peninsula. The noise immunity was ensured by adaptively changing the modulation method according to the measured level of the signal-to-noise ratio without changing the power of the transmitter in the direct channel. In order to reduce interference, it has been proposed and implemented to reduce the power of the main radio transmitter in the direct channel, but to ensure reliable reception of the signal in the service area, the use of a booster has been proposed and implemented. Due to these proposals and applications, a cable television distribution network has been established in the territory under consideration. Ilham Afandiyev1b, Elvin Muradsadeh1c